Knowledge of Cervical Cancer Screening in Adult Women: Meta-Analysis - I Gusti Agung Ngurah Putra Pradnyantara; Indah Adhitama Chrisnanda (Masters Program in Public Health, 2022)
Background: Cervical cancer is the fourth common cancer worldwide and the second most common cancer cases in women. Cervical cancer screening allows detection of abnormal cervical cells. Having knowledge about cervical cancer and its screening can increase the absorption of services for cervical cancer screening. This study was aimed to determine the comparison of participation in cervical cancer screening in adult women with high education with adult women with low education. Subjects and Method: This study was a systematic review and meta-analysis with the following PICO, population: adult women. Intervention: high knowledge. Comparison: low knowledge. Results: cervical cancer screening. The articles used in this study were obtained from two databases, namely Google Scholar and Pubmed. Keywords to search for